Measuring Lean Culture: Designing a Research Instrument - Osman, Azim Azuan; Nordin, Norani; Abd. Rahman, M.F. (Universiti Malaysia Pahang, 2021)
Transformation from conventional manufacturing system to lean manufacturing system has enabled many manufacturing companies to reduce waste and ultimately achieve operational excellence. Unfortunately, there were also many reported cases where manufacturers failed to sustain the transformation until they achieve the ultimate result. Converting organization’s culture into the lean culture is often claimed as one of the mechanisms to sustain lean transformation in manufacturing organizations. Thus, measuring to what level lean manufacturers have converted their organization’s culture relative to lean culture characteristics is critical. Selfadministered questionnaire is a practical research instrument to measure the level of lean culture in multiple manufacturing organizations that are located in far-reaching geographical as it saves time, money and effort. In this paper, 36 questionnaire items for measuring lean culture has been designed. These items can be used as parameters for predicting sustainability of lean transformation using statistical analysis such as linear regression or structural equation modelling